Fenologia da figueira-da-índia em Selvíria - MS - Segantini, Daniela Mota [UNESP] (2010)
The cactus pear is a cactaceous with Mexican origin and great productive potential for the edaphoclimatic conditions in Brazil, but for lack of knowledge, the culture is still little cultivated. With the objective to evaluate the phenology of cactus pear, the present research was realized in plants with 4 years of age, in spacing of 1.0 × 2.5 m, in the experimental area of Fazenda de Ensino, Pesquisa e Extensão da Faculdade de Engenharia de Ilha Solteira - UNESP, located in Selvíria - State of Mato Grosso, during August 2006 to January 2007. The experimental design was completely randomized, with ten replications and one plant by experimental plot that was evaluated: phenology and growth of fruits. The period of bud emission concentrated in the months of September and October. The flowering occurred 30 days after the bud flower emission. The fruits reached physiological maturity (harvest point) after 66 days from flowering and after 72 days of flowering the fruits were ready. The period of fruit development, since the emission of the flower bud to the physiological maturity was 96 days. The fruit growth curve was a quadratic function. The culture of the cactus pear can be an alternative, especially for small producers, because do not require large investments for the implementation and conduction, besides to present a good adaptation to the environmental conditions of our country. The fruits have excellent prices in national and international market and the utilization with sweets and jellies can increase the income of the producers.